A Novel Optical Quantal Analysis of Miniature Events Reveals Enhanced Frequency Following Amyloid β Exposure - Taylor, Henry B. C.; Tong, Rudi; Jeans, Alexander F.; Emptage, Nigel J. (Frontiers in Cellular Neuroscience, 2020)
Non-evoked miniature release of neurotransmitters is increasingly recognized as playing an important role in neural function and is implicated in synaptic plasticity, metaplasticity, and homeostasis. Spontaneous miniature release events (minis) are usually measured electrophysiologically by recording the miniature postsynaptic currents (mEPSCs) that they evoke. However, this indirect technique can be confounded by changes within the postsynaptic neuron. Here, using the fluorescent probe SynaptopHluorin 2×, we have developed an optical method for the measurement of minis that enables direct assessment of release events. We use the technique to reveal that the frequency of minis following incubation of hippocampal neurons with Amyloid β oligomers (Aβo) is increased. Electrophysiological mEPSC recordings obtained under the same conditions report a decrease in frequency, with the discrepancy likely due to Aβo-induced changes in quantal size. Optical quantal analysis of minis may therefore have a role in the study of minis in both normal physiology and disease, as it can circumvent potential confounds caused by postsynaptic changes.